Identifying key parameters for school bus monitoring system using a triangulation method: a study in Zanzibar - Said, Intisaar Omar; Abdul Raziff, Abdul Rafiez; Mahmod Attar Bashi, Zainab Senan; Shah, Asadullah (IEEE, 2026)
The design and development of school bus monitoring systems require a clear understanding of the key parameters that ensure student safety, reliable communication and parental satisfaction. While various studies have proposed technological solutions to improve school bus transportation safety, they often do not clearly identify the key parameters required for school bus monitoring systems. This study aimed to identify the critical parameters for such systems by first conducting the literature review which revealed three frequently referenced parameters which are student identification, bus location tracking, and SMS notification alerts. To validate the importance of these parameters in real world context, a triangulation method was applied, involving interviews with 2 school authorities, focus group discussion with 4 school bus drivers and questionnaire survey completed by 60 parents. Data was collected from the stakeholders in Zanzibar Urban West Region. The findings across all three methods confirmed that student identification, bus location tracking and SMS notification alerts are essential parameters for school bus monitoring systems. These validated parameters provide a strong foundation for designing and developing technological solutions for school bus monitoring.